Respuesta :
Answer:
y+5=-1/2(x+3)
Step-by-step explanation:
as perpendicular,
compare that given eqn with y-y1=m(x-x1),
m1=2
then,
perpendicular case,
m1×m2=-1
m2=-1/2
now,
as the eqn passes through point (-3,-5),
we know,
y-y1=m(x-x1)
then putting value,
y+5=-1/2(x+3)
Answer:
y + 5 = - [tex]\frac{1}{2}[/tex](x + 3)
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line.
y - 4 = 2(x - 6) is in this form with slope m = 2
Given a line with slope m then the slope of a line perpendicular to it is
[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{2}[/tex]
Hence the equation passing through (- 3, - 5) is
y - (- 5) = - [tex]\frac{1}2}[/tex] (x - (- 3)), that is
y + 5 = - [tex]\frac{1}{2}[/tex](x + 3) ← equation of perpendicular line